2020
DOI: 10.2147/hiv.s255549
|View full text |Cite
|
Sign up to set email alerts
|

<p>Relationship Between Food Insufficiency and HIV Infection Among Caregivers of Orphans and Vulnerable Children in Tanzania</p>

Abstract: Background: Although Tanzania experiences a general decline in HIV prevalence, some populations such as caregivers of orphans may be at a higher risk than the general population, suggesting that infection pathways still need further exploration. This study examines how food insufficiency relates to HIV infection among caregivers of orphans and vulnerable children (OVC) in Tanzania. Data and Methods: Data are from a community-based, USAID-funded Kizazi Kipya project that aims at increasing the uptake of HIV ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…We found that the majority of participants experienced food insecurity during the lockdown time. Food insecurity among MSM has been shown to be associated with lower rates of HIV testing (Nyirenda et al, 2018 ; Takada et al, 2020 ; Weinhardt et al, 2017 ; Wiss et al, 2021 ), higher new HIV infection (Amon Exavery et al, 2020 ), and potential violence in the community (Adhikari et al, 2020 ). It is important to improve the access to food secure care programs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the majority of participants experienced food insecurity during the lockdown time. Food insecurity among MSM has been shown to be associated with lower rates of HIV testing (Nyirenda et al, 2018 ; Takada et al, 2020 ; Weinhardt et al, 2017 ; Wiss et al, 2021 ), higher new HIV infection (Amon Exavery et al, 2020 ), and potential violence in the community (Adhikari et al, 2020 ). It is important to improve the access to food secure care programs.…”
Section: Discussionmentioning
confidence: 99%